2009
DOI: 10.1038/ijir.2009.57
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of exposure to a mobile phone on sexual behavior in adult male rabbit: an observational study

Abstract: The accumulating effects of exposure to electromagnetic radiation emitted by a conventional mobile phone (MP) on male sexual behaviour have not yet been analyzed. Therefore, we studied these effects in 18 male rabbits that were randomly divided into phone and control groups. Six female teasers were taken successively to the male's cage and the copulatory behavior was recorded. Serum total testosterone, dopamine and cortisol were evaluated. The animals of the phone group were exposed to MPs (800 MHz) in a stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…42 Nevertheless, this equilibrium is fragile and some studies have shown that the environment can also impact on it. Indeed, some stressors such as food restriction, [43][44][45] sleep deprivation [35][36][37][38][39] and exposure to the radiofrequency emitted by a conventional mobile phone 46,47 have been shown to be able to cause a stress sufficient enough to disturb it.…”
Section: Effect Of the Environment On The Endocrine Control Of Male Smentioning
confidence: 99%
“…42 Nevertheless, this equilibrium is fragile and some studies have shown that the environment can also impact on it. Indeed, some stressors such as food restriction, [43][44][45] sleep deprivation [35][36][37][38][39] and exposure to the radiofrequency emitted by a conventional mobile phone 46,47 have been shown to be able to cause a stress sufficient enough to disturb it.…”
Section: Effect Of the Environment On The Endocrine Control Of Male Smentioning
confidence: 99%
“…Lately many papers have been published on the effect of mobile phone exposure on human semen quality [Fejes et al, 2005;Agarwal et al, 2008] as well as experimental studies on sexual behavior and testicular function in rabbits [Salama et al 2008;Salama et al, 2009 a, b]. Studies have also been done on human EEG and sleep after such exposure [Hung et al 2007].…”
mentioning
confidence: 99%
“…[18][19][20] According to the authors, who allegedly performed their studies in a Japanese laboratory, the animals were kept squeezed in small cages for 8 h per day for 12 weeks during their 'exposure' from a mobile phone glued to the outside of the cage, under the rabbits' scrota. The mobile phones were set to the stand-by mode and thus did not produce any RF-EMF-there was no exposure!…”
Section: Impacts On Male Fertilitymentioning
confidence: 99%